Self-Assembly Behaviour of Amphiphile at Local Concentration: A Dissipative Particle Dynamics Simulation Study - Wu, Shaogui; Du, Tingting (Asian Journal of Chemistry, 2012)
A dissipative particle dynamics simulation technique is used to elucidate the self-assembly behavior of amphiphilic molecules at local high concentration. The initial state is setup by coating an amphiphile solution with a layer of water, which prevents the formation of crossing periodic configuration. The influence of the concentration of the amphiphile solution is investigated. At low concentration, amphiphilic molecules aggregate into a lot of micelles and small vesicles. With the increase of amphiphile concentration, vesicles with simple and complex structures are formed. A new vesicle formation pathway, which is slightly different from the classic vesicle formation pathway, is observed in current simulation condition. Vesicle is formed by the union of many large micelles directly instead of by bilayer-vesicle transition. At high concentration, complex vesicles with multichamber structures are formed. These chambers are separated by bilayer membranes and filled with solvent particles. The volume of complex vesicle as well as its chamber number is increasing with the initial concentration. Present simulation results are in well agreement with experimental result.